2019
DOI: 10.1038/s41419-019-2143-7
|View full text |Cite
|
Sign up to set email alerts
|

Aldo-keto reductases protect metastatic melanoma from ER stress-independent ferroptosis

Abstract: The incidence of melanoma is increasing over the years with a still poor prognosis and the lack of a cure able to guarantee an adequate survival of patients. Although the new immuno-based coupled to target therapeutic strategy is encouraging, the appearance of targeted/cross-resistance and/or side effects such as autoimmune disorders could limit its clinical use. Alternative therapeutic strategies are therefore urgently needed to efficiently kill melanoma cells. Ferroptosis induction and execution were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 52 publications
1
110
0
Order By: Relevance
“…Primer sequences are available in Supplementary Table 1. Gapdh mRNA level was used as an internal control and results were expressed as previously described 56 .…”
Section: Rna Extractiona and Real-time Pcrmentioning
confidence: 99%
“…Primer sequences are available in Supplementary Table 1. Gapdh mRNA level was used as an internal control and results were expressed as previously described 56 .…”
Section: Rna Extractiona and Real-time Pcrmentioning
confidence: 99%
“…It has been shown that ferroptosis-resistant cells upregulated NRF-2, which induced expression of an early ferroptotic marker glutathione-specific gamma-glutamylcyclotransferase 1 (CHAC1), and the aldo-keto reductases (AKRs) such as AKR1C1, AKR1C2, and AKR1C3 to degrade the lipid peroxides and prevent from ferroptotic cell death. Inhibition of AKR activity sensitized melanoma cells to ferroptosis confirming the role of these enzymes in prevention of ferroptosis induction [189]. In addition, NRF-2 has been implicated in UV-induced expression of PD-L1 in melanoma.…”
Section: Ferroptosis In Melanomamentioning
confidence: 66%
“…It has been hypothesized that chemosensitivity of OXPHOS high cancer cells could rely on ROS accumulation and might be potentially executed by induction of ferroptosis [188]. This suggests that a metabolic switch induced by BRAFi can sensitize melanoma cells to ferroptosis-inducing agents, and SCL7A11 has been suggested as a marker of the susceptibility of metastatic melanoma cells to ferroptosis [189]. In line with this, acute treatment with vemurafenib or trametinib reduced transcript level of SLC7A11 in BRAF V600E melanoma cells [190].…”
Section: Ferroptosis In Melanomamentioning
confidence: 89%
See 1 more Smart Citation
“…Our results highlighted an early activation of caspases, key mediators of the apoptotic program and responsible for PARP cleavage, in both cell lines but restricted to the combined SOR + STV regimen (Figure 2A, upper panels). The expected lower sensitivity of SK Mel 28 cells compared to CHL-1 is also evident, due to the presence of oncogenic BRAF V600E conferring less sensitivity to apoptotic stimuli [8,[29][30][31], evidenced by a less pronounced PARP cleavage efficiency at both 4 and 6 h post treatment compared to CHL-1. The involvement of the apoptotic pathway is also highlighted by the dramatic Mcl-1 downregulation in both cell lines exposed to SOR + STV (Figure 2A, middle/bottom panels), compared to control or each individual treatment (SOR or STV), both known to affect Mcl-1 expression [32][33][34][35].…”
Section: Apoptosis Is Involved In Combined Sorafenib/nutrient Restricmentioning
confidence: 91%